Multikulturalisme di Pesantren: Tantangan dan Peluang dalam Pendidikan Islam Kontemporer - Gozali; Fathurahman; Mahmud; Mohamad Erihadiana (South Sulawesi Education Development (SSED), 2024)
### Abstract This research explores how pesantren, as traditional Islamic educational institutions in Indonesia, respond to and integrate multicultural values into their curricula and activities. The study employs a qualitative approach, collecting data through in-depth interviews, direct observations, and document analysis from selected pesantren based on geographic variation and their educational approaches to multiculturalism. The findings indicate that pesantren view multiculturalism not only as a response to the ethnic, racial, and religious diversity in Indonesia but also as an expression of Islamic values that recognize diversity as divine will. In terms of curriculum, pesantren have taken proactive steps to integrate multiculturalism by including content that encompasses various cultures and civilizations in Islamic history and promoting significant non-Arab figures. Extracurricular activities, such as student exchanges, joint seminars with religious leaders from other faiths, and multicultural cultural festivals, are also focused on enhancing students' understanding and tolerance of diversity. However, the implementation of these multicultural values faces challenges, including internal resistance from community members who may see this as a threat to traditional Islamic values, as well as limitations in resources and external support. The research also identifies significant opportunities for further development, including the use of technology and collaboration with other educational institutions and international organizations to strengthen multicultural practices. Government support is considered crucial in helping pesantren enhance their multicultural capabilities. With the right approach, pesantren can play a vital role in shaping a more inclusive and adaptive understanding and practice of religion, which is essential to meet the needs of Indonesia's plural society today. Keywords: Multiculturalism, Islamic Education, Pesantren.